Pollinator Behaviour on a Food-Deceptive Orchid Calypso bulbosa and Coflowering Species. (12th March 2015) - Tuomi, Juha; Lämsä, Juho; Wannas, Lauri; Abeli, Thomas; Jäkäläniemi, Anne
Abstract : Food deception as a pollination strategy has inspired many studies over the last few decades. Pollinator deception has evolved in many orchids possibly to enhance outcrossing. Food-deceptive orchids usually have low pollinator visitation rates as compared to rewarding species. They may benefit in visitations from the presence (magnet-species hypothesis) or, alternatively, absence of coflowering rewarding species (competition hypothesis). We present data on pollinator visitations on a deceptive, terrestrial orchid Calypso bulbosa, a species with a single flower per plant and whose flowering period partly overlaps with rewarding, early flowering willows ( Salix sp.) and later-flowering bilberry ( Vaccinium myrtillus ). When surveying inactive bumblebee queens on willows in cool weather, about 7% of them carried Calypso pollinia. Most common bumblebee species appeared to visit and thus pollinate Calypso . Bumblebees typically visited one to three Calypso flowers before flying away, providing some support for the outcrossing hypothesis. We conclude that, regarding the pollinations strategy, both magnet-species and competition hypotheses have a role in the pollination of Calypso, but on different spatial scales. On a large scale rewarding species are important for attracting pollinators to a given region, but on a small scale absence of competition ensures sufficient pollination rate for the deceptive orchid.